Nephrotoxicity Risk of Cyclophosphamide in Lupus Model - Niken Indriyanti (Journal of Tropical Pharmacy and Chemistry, 2021)
Cyclophosphamide is one of the standard therapies for lupus, especially lupus nephritis based on its immunosuppressive effect. However, cyclophosphamide is also known as a nephrotoxic agent. Therefore, this research was aimed to measure the effect of cyclophosphamide at the dose that comparable to the human dose of 1 mg/kg BW on the kidney of lupus mice induced by means of 2,6,10,14-tetramethylpentadecane (TMPD). In this research, the IL-6 as a pro-inflammatory cytokine was tested by using flow cytometry method. In addition, the structural damage of the kidney tissues was assessed by means of Moroni’s kidney organ scoring method for lupus. The result showed that cyclophosphamide reduced the IL-6 significantly with the value of 36.72±22.79% for the TMPD-treated group; 32.59±9.97% for the cyclophosphamide group; and 30.25±4.48% for the naïve group. Moreover, the damages of the kidney tissues on the cyclophosphamide group were more severe than the TMPD-treated group. In conclusion, despite its anti-inflammatory effect which is useful for lupus, cyclophosphamide has a severe nephrotoxic effect which harms the patient. The effects may be a cause of the long interval use of cyclophosphamide. It can be a consideration for the further research and the next revision of the guideline for lupus nephritis treatment.